Recommendation Report on Campus Transit - Brown, Ethan; Carey, Madeleine; Lynn, Payton; Saia, Nick; Wells, Mia; Linenberger, Raegan; Roberts, Gage (My University, 2023)
The Kansas State University Student Governing Association (SGA), in coordination with the Flint Hills Area Transportation Agency (ATA), established the ATA Student Advisory Board. The Board identified the following goals: 1. Increase ATA’s engagement with and representation of students 2. Stabilize ATA’s pool of KSU funding sources 3. Preserve free-to-ride bus service for students